Mirrlees Meets Diamond-Mirrlees - Florian Scheuer; Iván Werning (Center for Economic Studies and ifo Institute (CESifo), 2016)
We show that the Diamond and Mirrlees (1971) linear tax model contains the Mirrlees (1971) nonlinear tax model as a special case. In this sense, the Mirrlees model is an application of Diamond-Mirrlees. We also derive the optimal tax formula in Mirrlees from the Diamond-Mirrlees formula. In the Mirrlees model, the relevant compensated crossprice elasticities are zero, providing a situation where an inverse elasticity rule holds. We provide four extensions that illustrate the power and ease of our approach, based on Diamond-Mirrlees, to study nonlinear taxation. First, we consider annual taxation in a lifecycle context. Second, we include human capital investments. Third, we incorporate more general forms of heterogeneity into the basic Mirrlees model. Fourth, we consider an extensive margin labor force participation decision, alongside the intensive margin choice. In all these cases, the relevant optimality condition is easily obtained as an application of the general Diamond-Mirrlees tax formula.
Keywords: 330